Optimization of an x-rays fluorescence spectrometer for analyzing a tantalite sample - Roveratti, Gabrielle; Bonotto, Daniel Marcos [UNESP] (My University, 2017)
X-rays fit the electromagnetic spectrum region between 0.1 and 100 Å. The X-rays fluorescence (XRF) analytical technique comprises the excitation process associated to the sample irradiation by a primary beam emanated from an X-rays tube. This method has been widely used to study the geochemistry of rocks, minerals and sediments, thus, reliable calibration steps are important to assure confidence on the data generated. This chapter reports several tests realized for this aim with S8 Tiger spectrometer from Bruker Co., belonging to LARIN (Ionizing Radiations Laboratory), UNESPetro (Geosciences Center Applied to Petroleum), IGCE-UNESP-Rio Claro (SP), Brazil. Petrobras acquired this equipment together with two software: QuantExpress (powdered samples) and GeoMaj (fused beads). The experiments were realized using a tantalite sample from the company Tantalite Ore Extraction Ltd. whose chemical composition is: Ta2O5 (44.91%), Al2O3 (4.55%), Fe2O3 (13.47%), MnO (4.31%), MgO (6.29%), and P2O5 (4.86%). QuantExpress software allowed the analysis of the major oxides commonly adopted in geochemical investigations: SiO2, Al2O3, Na2O, K2O, CaO, MgO, Fe2O3, TiO2, MnO, and P2O5. The tests adopted the recommended values for voltage and current under three analysis modes: Fast-3 minutes, Full-8 minutes, and Best-15 minutes. The sample weight also varied, corresponding to 2g, 4g, 6g, 8g and 10g. Simple statistical data treatment allowed finding the better experimental conditions for acquisition of the oxides concentration values.